Profil Kasus Kekerasan Seksual di Rumah Sakit Umum Pusat Dr. M. Djamil Padang Periode 2012 - 2016 - Hidayat, Taufik; Susanti, Rika; Manela, Citra; Sari, Noverika Winda; Syahputra, Abdullah Arief (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 9 No 1 (2019): Indonesian Journal Of Legal And Forensic SciencesDO - 10.24843/IJLFS.2019.v09.i01.p04, 2019)
Background  Forensic medicine plays an important role in solving the case of sexual violence. The objective of this study was to determine the profile of cases, victims and perpetrators of sexual violence who were examined in Dr. M. Djamil general hospital of Padang. Method  The design of the study was descriptive. Data were obtained from medical records of sexual violence cases in Dr. M. Djamil general hospital from 2012 to 2016. Results.  The highest number of sexual violence incident was in 2015 and the lowest was in 2013. The highest type of sexual violence was rape (39.3%). Children were the most frequent victims (76.4%). Most of the victims were junior high school students (22.9%). Most of the victims were not pregnant (92.1%) while hymen remains intact was about 17.1% , old torn (54.3%), new torn (10%) and 1 cases requires medical treatment (0.7%). We were conducted anal examination in 6 cases and found redness of anal in 1 case.  We were conducted sperm and semen analysis and found sperm in 9 vaginal swab of the victims (6.4%). We found redness of external genitalia (15%), laceration (5%), and abrasions (9.3%) and no injuries (70.7%) There were 9 cases that show the signs of violence, bruises in 5 victims (3.6%), abrasions in 2 victims (1.4%), and laceration in 1 victim (0.7%). The age of most perpetrators in this study was adults (59.3%). Closefriend is probably the perpetrators of sexual violence (27.1%). Conclusion  In this study rape is the most sexual violence cases and the majority of victims were children. Signs of violence were found in most cases and most perpetrators were closefriends. Keywords : sexual violence, rape, forensic